Tracking Water Splitting Activity by Cocatalyst Identity in SrTiO3 - Nursaya Zhumabay; Jeremy A. Bau; Rafia Ahmad; Laurentiu Braic; Huabin Zhang; Luigi Cavallo; Magnus Rueping (Small Structures)
Photocatalytic water splitting is the most idealistic route to green hydrogen production, but the extensive material requirements for this reaction make it difficult to realize good photocatalysts. Noble metal cocatalysts are often added to photocatalysts to aid in charge separation and improve surface kinetics for H2 evolution. Herein, the high activity of the promising photocatalyst Al‐doped SrTiO3 is demonstrated to be ultimately dependent on the cocatalyst used as much as the presence of Al dopant. By tracking the band energetics of photocatalyst electrodes using operando electrochemical attenuated total reflectance surface‐enhanced infrared absorption spectroscopy, cocatalysts (especially Rh) are found to shift the quasi‐Fermi levels and metal‐semiconductor flat‐band potentials of photocatalysts in an anodic direction. Furthermore, the size of the shift directly correlates with overall water splitting activity, demonstrating that SrTiO3 becomes more active as photogenerated electrons are stabilized further from the conduction band. Rh on Al‐doped SrTiO3 provides the most advantageous band tailoring as confirmed by density functional theory and is experimentally found to provide this effect by eliminating Ti3+‐related surface traps in the presence of Al dopants. Therefore, the effect of cocatalysts on water splitting activity is more complicated than previously thought.